1981
DOI: 10.3109/00365528109181030
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Propranolol on Insulin-stimulated Gastric Secretion in Dogs

Abstract: The effect of beta-adrenergic blockade on the insulin hypoglycemia-induced gastric secretion was studied. Insulin-stimulated (0.15 IU/kg) gastric acid and pepsin output and serum gastrin were measured before and after beta-adrenergic blockade with propranolol (20 microgram/kg/min intravenous infusion) in gastric fistula and Heidenhain pouch dogs. Insulin injection caused acid and pepsin secretion from the gastric fistula, and both acid and pepsin secretion was significantly increased during beta-adrenergic blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1987
1987

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Betaadrenoceptor-mediated inhibitory effects have previously been described concerning reflex vagal stimulation of gastric H+ secretion (Yamaguchi et al 1977, McCloy et al 1979, Grabner et al 1981), but also excitatory or no effects are reported (Kaess et al 1975, Christensen & Stadil 1976, Etzel et al 1982, Graffner & Jarhult 1984. Thus, at least during the present experimental conditions, alpha-adrenoceptors seem to be involved to only a minor degree in the control of H+ secretion.…”
Section: Discussionmentioning
confidence: 93%
“…Betaadrenoceptor-mediated inhibitory effects have previously been described concerning reflex vagal stimulation of gastric H+ secretion (Yamaguchi et al 1977, McCloy et al 1979, Grabner et al 1981), but also excitatory or no effects are reported (Kaess et al 1975, Christensen & Stadil 1976, Etzel et al 1982, Graffner & Jarhult 1984. Thus, at least during the present experimental conditions, alpha-adrenoceptors seem to be involved to only a minor degree in the control of H+ secretion.…”
Section: Discussionmentioning
confidence: 93%